2013
DOI: 10.33338/ef.8981
|View full text |Cite
|
Sign up to set email alerts
|

Range expansion of <i>Trichoferus campestris</i> (Faldermann) (Coleoptera: Cerambycidae) in Europe with the confirmation of its presence in Romania

Abstract: The distribution of the alien longhorn beetle Trichoferus campestris in Europe is analyzed based on new and published data. A literature review revealed that the number of records of this species has increased during recent years. According to the geographic range of these records and their temporal distribution, the species might be already established in several European countries and is quickly spreading west. It is also confirmed in Romania based on specimens collected in different localities from the extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…According to Fujita et al (2018), this species has been a non-natural fauna element in Japan. Some researchers (EPPO 2008;Grebennikov et al 2010;Dasc alu et al 2013) have also suggested Central Asian areas (Kazakhstan, Kyrgyzstan, Uzbekistan, Tadjikistan and eastern Russian up to the Ural Mountains) where the pest could be native. This latter statement could be controversial, because there are some references from these countries, in which the species was mentioned as a new fauna element or an unknown phytosanitary risk.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…According to Fujita et al (2018), this species has been a non-natural fauna element in Japan. Some researchers (EPPO 2008;Grebennikov et al 2010;Dasc alu et al 2013) have also suggested Central Asian areas (Kazakhstan, Kyrgyzstan, Uzbekistan, Tadjikistan and eastern Russian up to the Ural Mountains) where the pest could be native. This latter statement could be controversial, because there are some references from these countries, in which the species was mentioned as a new fauna element or an unknown phytosanitary risk.…”
Section: Resultsmentioning
confidence: 99%
“…Both the wide range of potential hosts and global warming have been equally implicated (Dascălu et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, adults have been caught in trap surveys in ports in Italy and Austria (Pennacchio et al ., 2016; Hoch et al ., 2016). Populations of T. campestris exist in East and Central European countries, such as the Ukraine, Romania and Hungary; T. campestris is considered likely to have spread westward from Asia north of the Black Sea (Dascalu et al ., 2013; Keszthelyi et al ., 2019). T. campestris was placed on the EPPO A2 list (i.e.…”
Section: Introductionmentioning
confidence: 99%